1997
DOI: 10.1002/(sici)1097-0215(19970917)72:6<1034::aid-ijc19>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential motile response of human malignant mesothelioma cells to fibronectin, laminin and collagen type IV: The role of β1 integrins

Abstract: β1 integrins are widely expressed in human tissues but their presence and function on malignant mesothelioma cells have not been examined. In this study, we have investigated the expression and function of β1 integrins in 7 human malignant mesothelioma cell lines. Immunofluorescence staining and FACS analysis showed similar expression of β1 integrins with strongest expression of α3β1 in all investigated mesothelioma cell lines. Using the Boyden chamber assay, we found that mesothelioma cell lines migrated to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
(31 reference statements)
4
24
1
Order By: Relevance
“…Klominek and co-workers previously showed that integrins are expressed in MM cell lines and that they mediate migration to ECM proteins, including collagen type IV, fibronectin, and laminin [94]. Koukoulis et al studied 22 clinical specimens of MM and found that the expression of most integrins, including the a6b4 integrin, in epithelioid MM is similar to previously reported patterns in AC of lung, and often other origins [95].…”
Section: Adhesion Molecules and Other Membrane Receptorssupporting
confidence: 58%
“…Klominek and co-workers previously showed that integrins are expressed in MM cell lines and that they mediate migration to ECM proteins, including collagen type IV, fibronectin, and laminin [94]. Koukoulis et al studied 22 clinical specimens of MM and found that the expression of most integrins, including the a6b4 integrin, in epithelioid MM is similar to previously reported patterns in AC of lung, and often other origins [95].…”
Section: Adhesion Molecules and Other Membrane Receptorssupporting
confidence: 58%
“…Klominek and co-workers previously showed that integrins are expressed in MM cell lines and that they mediate migration towards ECM proteins, including collagen type IV, fibronectin and laminin (Klominek, 1997). Koukoulis et al studied 22 clinical MM specimens and found that the expression of most integrins, including the α6β4 integrin, in epithelioid MM is similar to previously reported patterns in AC of the lung, and often of other origins (Koukoulis, 1997).…”
Section: Adhesion Molecules and Other Membrane Receptorsmentioning
confidence: 99%
“…Integrins and CD44 interact with an array of extracellular matrix (ECM) components, including collagen, fibronectin, laminin, vitronectin, and hyaluronan (HA), respectively (Etoh et al, 1992;Danen et al, 1993;Aznavoorian et al, 1996;Goebeler et al, 1996;Klominek et al, 1997), simultaneously acting as structural links from the cytoskeleton to the ECM as well as signaling molecules (Lokeshwar et al, 1994;Clark and Brugge, 1995;Entwistle et al, 1996;Cox and Huttenlocher, 1998).…”
Section: Introductionmentioning
confidence: 99%